Rencana Strategis Pengembangan Pusat Kanker Nasional Indonesia, Sebuah Studi Kasus - Panigoro, Sonar Soni (UI Scholars Hub, 2014)
Cancer is a chronic disease and its prevalence is increasing nowadays. Uptudate, Indonesia doesn’t have a comprehensive program for National Cancer Control. This study aims to develop a strategic plan for the development of National Cancer Center for Indonesia. This study is conducted by using operational research approach, and is conducted during the months of March to December 2013 by involving various stakeholders. In Indonesia, cancer is the third killer disease among the NCD (Non Communicable Disease), the incidence is increasing as well as the funding for cancer treatment. All informants expressed the importance of establishing a national institute that plays a role in cancer control in a comprehensive manner. The most ideal institute is a non structural form and to achieve it, a National Cancer Center Development Team to be formed that coordinates with the Director of Cancer Hospital